Humic acids induce growth and protection against water stress in corn native to Mexico: Humic extracts against abiotic stress - Hernández-Campos, Reinier; Robles, Celerino; Calderín-García, Andrés; Castañeda-Hidalgo, Ernesto; Muñiz-Becerá, Sahylin; Perez-Alvares, Sandra (Ecosistemas y Recursos Agropecuarios, 2024)
Under controlled conditions, it has been shown that the application of humic substances (HS) favors the growth and development of plants. However, scientific evidence in rainfed cropping in open field has been poorly documented. The objective of this research, carried out at the IPN-CIIDIR Oaxaca in 2019, was to characterize the humic acids (HA) extracted from vermicompost of urban solid waste using chemical and spectroscopic techniques, and to evaluate the effect of its root application on the reproductive stage, with continuous irrigation and with induced water deficit, in three selections of native maize (Zea mays L.) from three regions of Oaxaca, Mexico, grown under field conditions. The HA promoted higher values in plant height, stem diameter, and production of root and shoot biomass, in the presence of irrigation and with induced water deficit. The relative content of water and proline was also stimulated, as well as the content of chlorophylls a, b, and (a+b). The negative effects caused by an induced water stress were attenuated by the application of HA. HA from municipal solid waste vermicompost stimulated growth parameters in the reproductive phase and induced stress protection when irrigation use was limited.
Keywords: Humic substances; rainfed crop; reproductive stage; water stress; Zea mays L.